Effects of lead exposure before pregnancy and dietary calcium during pregnancy on fetal development and lead accumulation. - Han, S (2000)
Millions of women of child-bearing age have substantial bone lead stores due to lead exposure as children. Dietary calcium ingested simultaneously with lead exposure can reduce lead absorption and accumulation. However, the effects of dietary calcium on previously accumulated maternal lead stores and transfer to the fetus have not been investigated. We studied the effects of lead exposure of female rats at an early age on fetal development during a subsequent pregnancy. We gave 5-week-old female Sprague-Dawley rats lead as the acetate in their drinking water for 5 weeks; controls received equimolar sodium acetate. This was followed by a 1-month period without lead exposure before mating. We randomly assigned pregnant rats (n = 39) to diets with a deficient (0.1%) or normal (0.5%) calcium content during pregnancy. A total of 345 pups were delivered alive. Lead-exposed dams and their pups had significantly higher blood lead concentrations than controls, but the concentrations were in the range of those found in many pregnant women. Pups born to dams fed the calcium-deficient diet during pregnancy had higher blood and organ lead concentrations than pups born to dams fed the 0. 5% calcium diet. Pups born to lead-exposed dams had significantly (p<0.0001) lower mean birth weights and birth lengths than controls. There were significant inverse univariate associations between dam or pup organ lead concentrations and birth weight or length. The 0.5% calcium diet did not increase in utero growth. Stepwise regression analysis demonstrated that greater litter size and female sex were significantly associated with reduced pup birth weight and length. However, lead exposure that ended well before pregnancy was significantly (p<0.0001) associated with reduced birth weight and length, even after litter size, pup sex, and dam weight gain during pregnancy were included in the regression analysis. The data demonstrate that an increase in dietary calcium during pregnancy can reduce fetal lead accumulation but cannot prevent lead-induced decreases in birth weight and length. The results provide evidence that dietary nutrients can influence the transfer of toxins to the fetus during pregnancy. If these results are applicable to women, an increase in diet calcium during pregnancy could reduce the transfer of lead from prepregnancy maternal exposures to the fetus.